Modelling and optimization of rebound resilience and hardness of defatted rice bran/calcium carbonate-filled NR vulcanisates - Sompop Moonchai (2018)
Hardness and rebound resilience of natural rubber (NR) vulcanisates filled with defatted rice bran (DRB)/calcium carbonate (CaCO 3 ) were modelled and optimized. Second-order polynomial functions were generated to model the properties and to generate contour plots. Predicted properties of NR vulcanisates showed good agreement with experimental results. Hardness of filled-NR vulcanisates increased with filler loading, whereas rebound resilience decreased. At a fixed hardness level, lower CaCO 3 loading can be used with partial DRB replacement. DRB incorporation into rubber compounds can improve their stiffness. Contour plots were used to identify DRB and CaCO 3 level ranges for achieving optimum hardness and rebound resilience. © 2013 Elsevier Ltd. All rights reserved.